Geneva - Armitage, Richard, 1971- (Pegasus Crime, 2023)
A Nobel Prize-winning scientist who is suffering from the early stages of Alzheimer's is invite to a prestigious conference in Geneva to meet a enigmatic neuroscientist who has developed technology that could change medicine forever and also save her life.